Student Worksheets (LKPD) With Problem Based Learning (PBL) Model On Social Arithmetic Materials In Class VII SMP/MTs - Tussholeha, Zakia; Rezeki, Sri; Suripah, Suripah (AlphaMath : Journal of Mathematics Education, 2023)
This research is a development research that aims to produce learning tools with Problem Based Learning (PBL) model. Learning tools developed in the form of Student Worksheets (LKPD). Mathematical material used in this study is social arithmetic material. This study uses an R & D development method with a 4-D model which has several stages, namely (1) Define , (2) Design , (3) DevelopÂ  , (3) Disseminate . The instrument for collecting research data was in the form of a student worksheet validation sheet which was validated by 2 lecturers of Mathematics Education FKIP UIR and 2 teachers of mathematics studies at SMPN 1 Siak Kecil and student response questionnaire sheets. The data collection technique used is the validity test of the student worksheets and the practicality test of the student worksheets. The analysis technique used is the validity technique and the practicality technique. From the results of the study, the results of the validation of the student worksheets were 92.44% with a very valid validation level. And the results of the practicality of student worksheets are 87.84% with a very practical level of practicality. Based on the results of this study, it can be concluded that the development of Student Worksheets with the Problem Based LearningÂ  (PBL) model on social arithmetic material in class VII SMP/MTs is very valid, very practical and suitable for use in the learning process.